119PThe impacts of dose-time-fractionation schedules on pathological complete response rate (pCR) and local recurrence (LR). (24th November 2019) - Jin, F; Zhou, J; Luo, H; Li, S; Tan, X; Wu, Y; Wang, Y
Abstract: Background: Waiting for the highest pCR is clinically relevant as this helps to choose the candidates for a watch–and–wait approach or local excision, identify the optimal operation timing, increase the chance of R0 resection, or improve disease–free survival and/or overall survival. Meanwhile, LR is a serious problem since it causes disabling symptoms, and successful salvage of pelvic recurrence is rarely possible. Therefore, this paper will investigate the impacts of dose fractionations of preoperative radiotherapy (RT) on pCR and LR for rectal cancer using three– or four–field conformal RT techniques. Methods: The PubMed, Embase, and Web of Science databases (2000 to May 2018) were systematically searched for evidence. To evaluate the dose–response relationship, logistic response curves were fitted for pCR values, and the linear regression model was fitted for risk reduction of LR as a function of biologic effective dose (BED). Results: Data from 8 comparative studies enrolling 14, 869 patients were analyzed for pCR. Higher radiation doses were associated with increased pCR. If pCR curve was fitted using BED as a covariate, the dose required for 50% response (D50 ) ranged from 68·3 to 108·0 Gy. If BED was corrected with RT overall treatment time, The pCR curves of the similar treatment regimens in special patient cohorts interacted at identical D50, 50.7, 59.0, or 70.9 Gy. Regarding LR risk, 31 studies were identified and yielded 7, 699 patients. Increasing RT doses was also associated with reduction in LR, and a linear dose–response effect of BED was seen on the risk reduction of LR. Each 1 Gy increase in BED would reduce LR by 1·36%, hence a hypothesis was proposed that a BED of approximately 73.5 Gy would need to achieve 100% LC. Conclusions: Higher radiation doses were associated with increased pCR and LR reduction. In the future, by means of dose–response curves and the available pCR and LR values, we could perhaps obtain the dose gap to achieve 50% pCR response and 100% LC, and predict the amplitude of clinical benefits through limited RT dose escalation. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.